A cognitive approach to simile-based idiomatic expressions - Galera Masegosa, Alicia (Círculo de Lingüística Aplicada a la Comunicación, 2013)
This paper provides a detailed analysis of some of the most frequent simile-based idiomatic expressions from a cognitive point of view. In our study we show the necessity to further develop conventional metaphoric and metonymic analysis into more complex patterns of interaction between the two. Furthermore, several metaphors may also interact in the cognitive processes that underlie the understanding of idiomatic expressions, making it necessary to approach many of our examples making use of metaphoric complexes. We will explore the ways in which motivation and transparency may vary in idioms that arise from the same ontological metaphor, both intralinguistically and cross-linguistically. In addition, we will regard hyperbole as a fairly pervasive phenomenon in simile-based idioms.